2008
DOI: 10.1093/jn/138.4.718
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Intake of a High-Protein Diet with or without Potassium Citrate Modulates Acid-Base Metabolism, but Not Bone Status, in Male Rats

Abstract: High dietary protein intake generates endogenous acid production, which may adversely affect bone health. Alkaline potassium citrate (Kcit)(2) may contribute to the neutralization of the protein-induced metabolic acidosis. We investigated the impact of 2 levels of protein intake and Kcit supplementation on acid-base metabolism and bone status in rats. Two-month-old Wistar male rats were randomly assigned to 4 groups (n = 30 per group). Two groups received a normal-protein content (13%) (NP) or a high-protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
5
26
0
1
Order By: Relevance
“…These results are consistent with previous observations in rats (16,21) that reported no change in femoral bone mass, macro-mineral composition, or urinary excretion of pyridinium crosslinks of collagen in response to a dietary protein excess, despite hypercalciuria. Zernicke et al (22) found a greater femoral neck percent ash in 8-wk-old rats fed a 30% protein diet (versus 15%), however, without any improvement regarding structural and material properties.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous observations in rats (16,21) that reported no change in femoral bone mass, macro-mineral composition, or urinary excretion of pyridinium crosslinks of collagen in response to a dietary protein excess, despite hypercalciuria. Zernicke et al (22) found a greater femoral neck percent ash in 8-wk-old rats fed a 30% protein diet (versus 15%), however, without any improvement regarding structural and material properties.…”
Section: Discussionsupporting
confidence: 93%
“…Calcium and magnesium concentrations in food, urine, and faecal samples were determined by atomic absorption spectrophotometry (AA800, Perkin Elmer, Norwalk, CT), as described previously (16). Then, calcium retention (mol/24 h), defined as [calcium intake Ϫ (urinary calcium excretion ϩ faecal calcium excretion)] was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the need of alkaline organic salts increased to neutralize the endogenous acid production associated with excessive protein intake. And the supplementation of potassium citrate in the diet for male rat neutralized the metabolic acidosis induced by high dietary protein intake (Mardon et al, 2008). The lower potassium requirement in our study seems to correlate to the lower dietary protein content, however, direct proofs should be further investigated.…”
Section: Discussionmentioning
confidence: 57%
“…There are some evidences suggesting that dietary protein level would influence the potassium requirement. Longterm higher dietary protein induced metabolic acidosis in male rat, which was neutralized by the supplementation of potassium citrate (Mardon et al, 2008). Li et al (2011) also reported that the gill Na + -K + ATPase mRNA expression increased with the dietary protein level in L. vannamei.…”
Section: Introductionmentioning
confidence: 96%